Kajian Yuridis Pengesampingan Pasal 1266 dan Pasal 1267 Kitab Undang-Undang Hukum Perdata Sebagai Syarat Batal Dalam Perjanjian Kredit Perbankan - Rocky Marciano Ambar; Budi Santoso; Hanif Nur Widhiyanti (UNIVERSITAS ISLAM KADIRI, 2017)
Banks in the redit agreement use more standardized credit agreements, the use of standard contracts in the banking credit agreement is based on 2 (two) things, (1) The existence of unbalanced position (berganing position) between banks and the debtor, the bank has a more dominant position than the debtor. (2) There is an understanding of the principle of freedom of contract absolutely and indefinitely so that the bank has absolute freedom to determine the form and content of the agreement. So banks can freely to determine the form and contents of the agreement included in the clause of the terms of void wanprestasi arranged to include mengesaampinkan Article 1266 and Article 1267 Civil Code in the agreement. Whereas the provision of Article 1266 of the Civil Code provides that in the event that the revocation of the treaty must be requested by the court and the judge through the decision of the court may determine the types of compensation for the parties. Based on the background, then as for the formulation of the problem of writing is (1). Whether the inclusion of clause 1266 and Article 1267 of the Civil Code in the credit agreement of the banking system has fulfilled the principle of equilibrium and justice. (2) What is the juridical implication of the inclusion of clauses which exclude Article 1266 and Article 1267 of the Civil Code in the credit agreement pertaining to the debtor's right in the process of settling the interpretation as a condition of cancellation of the agreement. The research method used is normative juridical research. The result of this research is the waiver of Article 1266 and Article 1267 of the Civil Code which regulates the waiprestasi void in the agreement and the types of indemnity is contrary to the principle of fairness and the principle of equilibrium. The principle of justice according to Rawls is that it is unfair to sacrifice the right of one or more persons only for the sake of greater economic gain and even justice must be understood as fairness, in the sense of